2016
DOI: 10.3390/scipharm84030523
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Analgesic Properties of Halogen-Substituted 4-Hydroxy-2,2-dioxo-1H-2λ6,1-benzothiazine-3-carboxanilides

Abstract: As potential new analgesics, the corresponding 4-hydroxy-2,2-dioxo-1H-2λ6,1-benzothiazine-3-carboxanilides have been obtained by amidation of ethyl 4-hydroxy-2,2-dioxo-1H-2λ6,1-benzothiazine-3-carboxylate with aniline and its halogenated analogsin boiling dry xylene. The peculiarities of the mass and nuclear magnetic resonance (1Н and 13С) spectra of the synthesized compounds are discussed. Using X-ray diffraction analysis, the ability of the compounds to form stable solvates with N,N-dimethylformamide has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…By the example of allyl [ 31 ], isopropyl ( Figure 3 ) and benzyl ( Figure 4 ) derivatives it has been conclusively proven that actually methyl 4-methyl-2,2-dioxo-1 H -2λ 6 ,1-benzothiazine-3-carboxylate ( 3 ) is alkylated exclusively at the nitrogen atom independently from the structure of alkyl halide. Simultaneously, it has been found that the tendency to form solvates with various organic solvents previously mentioned for 4-hydroxy-2,2-dioxo-1 H -2λ 6 ,1-benzothiazines over and over again [ 17 , 32 ] is also typical for their 4-methyl-substituted analogs. In particular, the ability of methyl 1-benzyl-4-methyl-2,2-dioxo-1 H -2λ 6 ,1-benzothiazine-3-carboxylate ( 5g ) to form a monosolvate easily from methanol already in crystallization has been found ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By the example of allyl [ 31 ], isopropyl ( Figure 3 ) and benzyl ( Figure 4 ) derivatives it has been conclusively proven that actually methyl 4-methyl-2,2-dioxo-1 H -2λ 6 ,1-benzothiazine-3-carboxylate ( 3 ) is alkylated exclusively at the nitrogen atom independently from the structure of alkyl halide. Simultaneously, it has been found that the tendency to form solvates with various organic solvents previously mentioned for 4-hydroxy-2,2-dioxo-1 H -2λ 6 ,1-benzothiazines over and over again [ 17 , 32 ] is also typical for their 4-methyl-substituted analogs. In particular, the ability of methyl 1-benzyl-4-methyl-2,2-dioxo-1 H -2λ 6 ,1-benzothiazine-3-carboxylate ( 5g ) to form a monosolvate easily from methanol already in crystallization has been found ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, our results can be regarded somewhat broader, for example, as the substantiation for involving not only esters described in the compounds under study, but 1-R-4-methyl-2,2-dioxo-1 H -2λ 6 ,1-benzothiazine-3-carboxylic acids as their basis, as well as various N -R-amides. Moreover, N -R-amides were specified as the most promising analgesics in the series of 4-hydroxy-2,1-benzothiazine analogs previously studied [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the possibility of the existence of the similar compounds in different tautomeric forms, a search of the Cambridge Structural Database (CSD Version 5.41, update of June 2022; Groom et al, 2016) for the benzothiazine fragment was performed. Of the 45 hits found, 19 reported the enol form of this fragment [refcodes: AKIJIP, AKIJIP01 (Ukrainets et al, 2016b), CABBEP (Lei et al, 2016), DUCBEL, DUCBEL01 (Shishkina et al, 2020b), IJUJAA (Ukrainets et al, 2015b), LANNUM (Ukrainets et al, 2016a), LOGHEW (Ukrainets et al, 2014a), MINJAW (Shishkina et al, 2013), NODGUK (Ukrainets et al, 2013), NOXJOC (Lei et al, 2019), RACQUL (Shishkina et al, 2020a), TAJXUB, TAJXUB01, TAJXUB02 (Ukrainets et al, 2020a), UWUCIA (Ukrainets et al, 2015a), XEKPUB (Ukrainets et al, 2017), ZUZJIQ, ZUZJOW (Ukrainets et al, 2020b)], while the keto form was detected in 12 hits [refcodes: KANTIE (Shafiq et al, 2011), LIVPUC (Tahir et al, 2008), LIVQAJ (Shafiq et al, 2008a), MOTDOP (Shafiq et al, 2009b), PONWEV (Shafiq et al, 2009d), SEJWAI (Shishkina et al, 2017), SOGDOI (Shafiq et al, 2008b), SOLKOU (Shafiq et al, 2009a), UZAMOZ (Ukrainets et al, 2014b), VACKER (Khan et al, 2010), WACRUP (Shafiq et al, 2010), YOVBER (Shafiq et al, 2009c)]. Both of these two forms are presented in structure NAKZAD (Lega et al, 2016c).…”
Section: Database Surveymentioning
confidence: 99%